A CNTFET universal mixed‐mode biquad active filter in subthreshold region. Issue 9 (24th October 2018) - Zanjani, S. Mohammad Ali; Dousti, Massoud; Dolatshahi, Mehdi
Abstract: This paper presents a new low‐voltage and low‐power mixed‐mode universal active filter, using only 12 carbon nanotube field effect transistors (CNTFETs) and 2 grounded capacitors to improve the noise performance of the proposed circuit. Due to the use of subthreshold transistors biased at ±0.2 V supply voltage, the power consumption of the proposed multi input‐single output (MISO) filter is only 850 nW at 19 MHz center frequency. On the other hand, relaxing from any matching components, the center frequency and quality factor of the proposed filter can be tuned electronically with low sensitivity to the values of the active and passive elements. Furthermore, the active chip area of the proposed filter is significantly reduced to 0.047 μm 2, in 32 nm CNTFET technology. Therefore, as the HSPICE simulation results show, the input referred noise values at 19 MHz are reduced to 15.5 nV/ Hz and 185 fA / Hz in voltage and current modes, respectively. It is also shown that, by changing the number of nanotubes in the CNTFET structure, a very good power‐frequency trade‐off can be achieved for low‐power GHz applications.